Application of Cognitive Defusion Group Counselling to Reduce Insecurity among Junior High School Students - Mimi Hasmiati; Bau Ratu; Azam Arifyadi; Hasan Hasan (Journal of General Education and Humanities, 2025)
This study aims to examine the effectiveness of Cognitive Defusion group counselling services in reducing students' levels of insecurity. The study employed a Guidance and Counselling Action (PTBK) design, which was conducted in two cycles with eight eighth-grade students serving as research subjects, selected through purposive sampling. Data were collected through questionnaires and interviews, and then analysed both descriptively and quantitatively. The results showed a significant decrease in insecurity levels, from 77.12% (high category) in the pre-cycle to 61% (medium category) in cycle I, and further decreased to 55.5% (low category) in cycle II. These findings suggest that the Cognitive Defusion technique is effective in helping students release negative thoughts, boost self-confidence, and enhance self-acceptance.